Arg-Phe-amide-related peptides influence gonadotropin-releasing hormone neurons?. - Kelestimur, Haluk; Kacar, Emine; Uzun, Aysegul; Ozcan, Mete; Kutlu, Selim (Wolters Kluwer Medknow Publications, 2013)
The hypothalamic Arg-Phe-amide-related peptides, gonadotropin-inhibitory hormone and orthologous mammalian peptides of Arg-Phe-amide, may be important regulators of the hypothalamus-pituitary-gonadal reproductive axis. These peptides may modulate the effects of kisspeptins because they are presently recognized as the most potent activators of the hypothalamus-pituitary-gonadal axis. However, their effects on gonadotropin-releasing hormone neurons have not been investigated. In the current study, the GT1-7 cell line-expressing gonadotropin-releasing hormone was used as a model to explore the effects of Arg-Phe-amide-related peptides on kisspeptin activation. Intracellular calcium concentration was quantified using the calcium-sensitive dye, fura-2 acetoxymethyl ester. Gonadotropin-releasing hormone released into the medium was detected via enzyme-linked immunosorbent assay. Results showed that 100 nmol/L kisspeptin-10 significantly increased gonadotropin-releasing hormone levels (at 120 minutes of exposure) and intracellular calcium concentrations. Co-treatment of kisspeptin with 1 mu mol/L gonadotropin-inhibitory hormone or 1 mu mol/L Arg-Phe-amide-related peptide-1 significantly attenuated levels of kisspeptin-induced gonadotropin-releasing hormone but did not affect kisspeptin-induced elevations of intracellular calcium concentration. Overall, the results suggest that gonadotropin-inhibitory hormone and Arg-Phe-amide-related peptide-1 may have inhibitory effects on kisspeptin-activated gonadotropin-releasing hormone neurons independent of the calcium signaling pathway.
Keywords: neural regeneration; hypothalamus; gonadotropin-inhibitory hormone; Arg-Phe-amide-related peptide-1; kisspeptin; gonadotropin-releasing hormone; calcium signaling; GT1-7 cells; neuroregeneration